THE ANALYSIS OF ELEMENTARY UNIVERSITY-STUDENTS‘ MISCONCEPTIONS IN BASIC SCIENCE CONCEPT UTILIZING THE CERTAINTY OF RESPONSE INDEX (CRI) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2020)
This study aims to determine the level of miscoCRInception of PGSD students in the Basic Conceptual Science course using the Certainty of Response Index (CRI). This research was conducted at UST using a population of class II H PGSD. The method used was descriptive analysis with data collection techniques through tests with CRI. The results showed the level of achievement of student conceptions in the basic science course subjects, 37.03% misconceptions, 28.91% knew the concepts, and 34.06% did not know the concepts. The highest misconception occurs in the structure and function of living things with a percentage of 31.5%.AbstrakPenelitian ini bertujuan untuk mengetahui tingkat miskonsepsi mahasisa PGSD pada mata kuliah Konsep Dasar IPA dengan menggunakan CRI Certainty of Response Index (CRI). Penelitian ini dilakukan d UST dengan menggunakan populasi mahasiswa PGSD kelas II H.  Metode yang digunakan adalah analisis deskriptif analisis dengan teknik pengumpulan data melalui tes dengan disertai  CRI. Hasil penelitian  menunjukkan tingkat pencapaian konsepsi mahasiswa pada mata kuliah konsep dasar IPA yaitu sebanyak 37,03% miskonsepsi, 28,91% tahu konsep, dan 34,06% tidak tahu konsep. Miskonsepsi tertinggi terjadi pada materi Struktur dan Fungsi Makhluk Hidup dengan persentase 31,5%.
Keywords: misconception; CRI; Science; PGSD; elementary university-students